2020
DOI: 10.2196/19006
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health App for Japanese Adult Patients With Asthma: Clinical Observational Study

Abstract: Background Inappropriate asthma control reduces quality of life and causes increased exacerbations. Mobile health (mHealth) employs information and communication technology for surveying health-related issues. Objective This noninterventional, observational study assessed current real-world asthma control levels among Japanese patients with asthma and cough variant asthma (CVA) using the Zensoku-Log app. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…Those taking weekly pictures had reduced gingivitis scores, whereas the other group showed no improvements, and their gum condition slightly deteriorated (the decline in the second group was not statistically significant). Similarly, other observational studies using mHealth apps in which the researcher does not provide any feedback have shown that the apps improve health (eg, reducing asthma attacks) [32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…Those taking weekly pictures had reduced gingivitis scores, whereas the other group showed no improvements, and their gum condition slightly deteriorated (the decline in the second group was not statistically significant). Similarly, other observational studies using mHealth apps in which the researcher does not provide any feedback have shown that the apps improve health (eg, reducing asthma attacks) [32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…Several apps supporting patients with chronic diseases or cancer have already been developed (19)(20)(21). In case of psoriasis in two randomized controlled trials, Sevendsen et al demonstrated that a smartphone app improved patients' adherence to topical treatment and Spencer et al showed that psoriasis patients learned more about their disease when using an app than a control group without digital support (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Japan is another country in which theophylline is widely prescribed. One study revealed that about 15% of patients with asthma were prescribed theophylline 6 . The therapeutic concentration of theophylline for asthma or COPD ranges from 10 to 20 µg/mL.…”
Section: Discussionmentioning
confidence: 99%